2014
DOI: 10.1007/s00345-014-1363-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of prior history of urothelial carcinoma of the bladder in patients with upper urinary tract urothelial carcinoma: results from a retrospective multicenter study

Abstract: Prior history of muscle-invasive UCB was significantly associated with an increased risk of disease recurrence and cancer-specific death in patients with UTUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
3
5
1
1
Order By: Relevance
“…Thus, smoking may play an important role in the occurrence of UTUCs. Additionally, our study confirmed that BC was a prognostic factor for UTUC, which is consistent with the findings of Nuhn [24]. This may be due to the similar pathogenesis of UTUC and BC or a missed diagnosis of UTUC in some BC patients (especially for ureteral TCCs).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, smoking may play an important role in the occurrence of UTUCs. Additionally, our study confirmed that BC was a prognostic factor for UTUC, which is consistent with the findings of Nuhn [24]. This may be due to the similar pathogenesis of UTUC and BC or a missed diagnosis of UTUC in some BC patients (especially for ureteral TCCs).…”
Section: Discussionsupporting
confidence: 92%
“…Third, the present study did not identify significant relationships between BRFS and known prognostic factors, such as concomitant bladder cancer and a history of bladder cancer (p>0.05, data not shown), which conflicts with previously reported data [1719]. This discrepancy may be related to differences in the cohorts or the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite these differences, the common factors in both groups were pathologic T2 to T4 stages, multifocal ureteral tumors, concomitant bladder lesions, and intravesical instillation. Similar results have been reported in previous studies of the prognostic factors for UTUC [21516171819].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies indicated that UTUC patients with history of bladder tumor was an independent predictor of IVR but had no effect on non-bladder recurrence or CSS (6-8). Nuhn et al (16) showed that previous MIBC rather than NMIBC was an independent risk factor for CSS. It should be noted that these studies were usually based on relatively small sample size and short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%